Current status of laparoscopic bariatric/metabolic surgery in Japan: The sixth nationwide survey by the Japan Consortium of Obesity and Metabolic Surgery. Issue 2 (21st July 2020) - Ohta, Masayuki; Kasama, Kazunori; Sasaki, Akira; Naitoh, Takeshi; Seki, Yosuke; Inamine, Susumu; Oshiro, Takashi; Doki, Yuichiro; Seto, Yasuyuki; Hayashi, Hideki; Uyama, Ichiro; Takiguchi, Shuji; et al.
Abstract: Introduction: Laparoscopic bariatric procedures have been performed in Japan since 2000. Laparoscopic sleeve gastrectomy (LSG) has been fully covered by National Health Insurance since 2014, and it has been increasingly performed recently. The Japan Consortium of Obesity and Metabolic Surgery conducts a nationwide survey on laparoscopic bariatric/metabolic surgery every 2 years. Methods: The survey was sent by post or email to 97 Japanese institutions in January 2020. Results: From 2000 to 2019, a total of 3669 laparoscopic bariatric/metabolic procedures were performed in 64 institutions. The most popular procedure was LSG (n = 2866), followed by LSG with duodenojejunal bypass (LSG‐DJB, n = 337) and laparoscopic Roux‐en‐Y gastric bypass (LRYGB, n = 280). Morbidity and reoperation rates were, respectively, 29.8% and 11.8% for LRYGB, 16.8% and 2.8% for LSG, and 13.6% and 6.6% for LSG‐DJB. At 5 years after the procedures, the percentage of excess weight loss was 78% for LRYGB, 66% for LSG, and 80% for LSG‐DJB. Conclusion: This nationwide survey clearly showed that laparoscopic bariatric/metabolic surgery has been safely and effectively performed for 20 years in Japan.